A comparative study on performance, combustion and emission characteristics of diesel engine fuelled by biodiesel blends with and without an additive. (1st August 2018) - Musthafa, M. Mohamed; Kumar, T. Ashok; Mohanraj, T.; Chandramouli, R.
Highlights: Cetane number improver-di- tert -butyl peroxide (DTBP) is used an additive. Palm oil methyl ester blend with diesel in 20:80 by volume as the test fuel. 1% of DTBP by volume is added to B20 blend as another test fuel. Comparative study was made between two test fuels in reference with diesel fuel. NOx emission was significantly reduced for additive added B20 blend fuel. Abstract: Biodiesel is a fuel containing mono-alkyl esters which are derived from vegetable oils or animal fats. Biodiesel fuels are well-adopted now a day's having multiple benefits such as a renewable energy source, less pollutant emissions of carbon monoxide, hydrocarbons and particulate matter and so on. The oxides of nitrogen (NOx ) emissions reported in the literature are ambiguous for biodiesel blended fuels with reference to baseline diesel NOx . Authors have come out with different conclusions of no change in NOx, a decrease NOx and an increase in NOx . This study aims to reduce NOx emission of palm oil methyl ester blended with diesel fuel (B20), by using Cetane number improver-di- tert -butyl peroxide (DTBP) and to improve ignition performance of the test fuel. Single cylinder, four stroke, water cooled diesel engine loaded by eddy current dynamometer was used for this study. The engine was run with diesel, B20 fuel and B20 with 1% DTBP additive by volume basis. The performance, combustion and emission results were compared. The results revealed that B20 with additives shows an increased thermal efficiency by 2–3.5% and decrease specific energy consumption by 10–15% compared to diesel and B20 fuel. Significant reduction of CO and NOx in trade off with slight increase in HC for the B20 fuel without additives was observed.